Sex Trafficking of Black Girls: A Critical Race Theory Approach to Practice. Issue 1 (2nd January 2022) - Constance-Huggins, Monique; Moore, Shaneé; Slay, ZaDonna M.
ABSTRACT: Child sex trafficking is a troubling, yet hidden, social problem in the United States. Black girls are particularly vulnerable given the intersection of their race and gender as they navigate biological, psychological, and social vulnerabilities. Yet, little light is shed on their experiences, and consequently, strategies to practice with them are lacking. To resist the universal focus on sex trafficking, and to develop targeted approaches to address marginalized groups, such as Black girls, it is imperative to embrace critical, non-exclusionary, and non-oppressive perspectives. This paper introduces critical race theory (CRT) and employs some of its tenets to explain the oppression that Black girls face. Finally, it provides practice strategies, grounded in CRT, to meet the unique challenges of Black girls thereby advancing social work practice in an increasingly racialized context.